Antithrombotic Medication Use and Bleeding Risk in Medically Ill Patients After Hospitalization. (September 2013) - Mahan, Charles E.; Spyropoulos, Alex C.; Fisher, Maxine D.; Fields, Larry E.; Mills, Roger M.; Stephenson, Judith J.; Fu, An-Chen; Klaskala, Winslow
Background: Hospitalized medically ill patients receiving antithrombotic medications experience increased risk of bleeding. We examined antithrombotic use, bleeding rates, and associated risk factors at 30 days post discharge. Methods: This retrospective database analysis included nonsurgical patients aged ≥40 years hospitalized for ≥2 days during 2005 to 2009. Previously cited, validated International Classification of Diseases, Ninth Revision, Clinical Modification codes for major bleeding were used to define clinically relevant bleeding. Results: Of the 327, 578 patients, 9.1% received antithrombotic medications, of which 3.7% were anticoagulants. Rates of major and minor bleeding were 1.8% and 7.1%, respectively. Preindex gastroduodenal ulcer, thromboembolic stroke, blood dyscrasias, liver disease, and rehospitalization were the strongest predictors of major bleeding. Other risk factors included increasing age, male gender, and hospital stay of ≥3 days. Conclusions: Careful consideration of these demonstrated bleed-associated comorbidities before initiating anticoagulation or combining antithrombotic medications in medically ill patients may improve strategies for prevention of postdischarge thromboembolism.